Characterization of specific effort in female wrestlers: lactacidemia, FC, VFC and rate of perceived effort (BORG) - Pintos-Figueroa, P. R.; Carballeira-Fernandez, E.; Dopico-Calvo, X.; Castro-Seoane, I.; Castro-Seoane, N.; Iglesias-Soler, E. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
The characterization of the effort will mark the lines of work. Heart Rate Variability (HRV) is the result of interactions between the autonomic nervous system-SNA- (with its sympathetic-vagal balance) and the cardiovascular system. The relationship between Lactate and Borg values is directly related to the literature. The PURPOSE of this work was to describe and characterize the effort during an Olympic Fights match and to relate the analyzed parameters. METHODS: 9 female wrestlers (n=9), members of the national wrestling team in the cadet and junior categories (age n=16,33, SD=0;71 ), were the object of study, during 3 days of testing. All subjects performed the same tests: first day recording baseline HR, second day baseline HR recording and a standardized training with a real monitored Olympic Wrestling match. The third day: baseline HR recording. With all this we obtained the values of VFC, Lactate and Borg scale during the confrontation. The time constant of the approximation of heart rate recovery was also analyzed by an interactive monoexponential regression process. RESULTS: The Lactate peak was at minute 3 (Mean: 14.03 mmol / l and SD: 3.5). The values of the BORG scale were higher at the end of the second round (p <0.001). High and significant correlations were detected between the perception of effort and lactacidemia (p 0.005) in all cases; CONCLUSIONS: A high glycolytic involvement in the Olympic wrestling match is confirmed. The Borg scale can be a useful tool for monitoring the intensity of combat. A single confrontation is insufficient to generate changes in HRV.